Pemanfaatan Ikan Sapu-Sapu (Hyspostosmus sp) Sebagai Pakan Ikan Di Danau Tempe - Ainul Yuniar (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The results showed that the use of broom fish as fish feed in Tempe Lake, Tempe sub-district, Wajo Regency, had a high nutritional content. The content of broom fish is 37.07 ± 3.50 % crude protein, 16.85 ± 4.35% crude fat, 1.92 ± 1.09% crude fiber, 33.25 ± 3.99% ash and gross energy 4559 ± 1244.37 kcal/g. The results of the analysis carried out, mixing feed with broom fish meal was better than without using broom fish meal. Study. The purpose of this study was to determine the feed formulation of broom fish (Hyspostosmus sp) and to determine the chemical quality of fish feed in Lake Tempe. The research method used an experimental research approach with a quantitative approach in analyzing the data obtained and described in the form of numbers. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and each treatment was repeated three times, so that 12 experimental units were obtained. This research was conducted at the Laboratory of Chemistry and Animal Feed, Hasanuddin University. broom fish can be used as raw material for making feed which can be pursued by making homemade feed through simple techniques by utilizing relatively cheap sources of raw material for broom fish in Lake Tempe.